2013
DOI: 10.1002/jgrb.50063
|View full text |Cite
|
Sign up to set email alerts
|

Mantle flow in subduction systems: The mantle wedge flow field and implications for wedge processes

Abstract: [1] The mantle wedge above subducting slabs is associated with many important processes, including the transport of melt and volatiles. Our understanding of mantle wedge dynamics is incomplete, as the mantle flow field above subducting slabs remains poorly understood. Because seismic anisotropy is a consequence of deformation, measurements of shear wave splitting can constrain the geometry of mantle flow. In order to identify processes that make first-order contributions to the pattern of wedge flow, we have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 133 publications
(280 reference statements)
8
109
0
Order By: Relevance
“…There are large variations in average delay times for these slab zones, with some zones exhibiting relatively weak seismic anisotropy (e.g., JAP and SMA DSZs) and some others exhibiting delay times up to *2 s (e.g., JAV1 and KUR DSZs). This is consistent with the complex spatial variations of shear wave splitting patterns in most mantle wedges worldwide concluded by Long and Wirth (2013). The correlations of the average delay time dt with convergence rate V c , as well with DSZ's subduction angle a DSZ , were analyzed (Fig.…”
Section: Average Delay Time and Dszssupporting
confidence: 85%
“…There are large variations in average delay times for these slab zones, with some zones exhibiting relatively weak seismic anisotropy (e.g., JAP and SMA DSZs) and some others exhibiting delay times up to *2 s (e.g., JAV1 and KUR DSZs). This is consistent with the complex spatial variations of shear wave splitting patterns in most mantle wedges worldwide concluded by Long and Wirth (2013). The correlations of the average delay time dt with convergence rate V c , as well with DSZ's subduction angle a DSZ , were analyzed (Fig.…”
Section: Average Delay Time and Dszssupporting
confidence: 85%
“…However, seismic anisotropy data, 3-D numerical modeling, and experimental studies have shown that mantle flow in subduction zones may be much more complex, especially at and near the terminations of the arcs (Kneller and van Keken, 2008;Long and Silver, 2009;Long and Wirth, 2013;MacDougall et al, 2014;Schellart, 2010Schellart, , 2004. Because the compositions of primary arc magmas reflect the composition of the mantle wedge (variably modified by slabderived components), spatial variations in the geochemistry of arc magmas provide independent evidence for circulation patterns in the mantle wedge.…”
Section: Introductionmentioning
confidence: 97%
“…1) (Savage, 1999;Park and Levin, 2002;Long and Silver, 2008;Long, 2013;Long and Wirth, 2013;Wang and Zhao, 2013;Zhao et al, 2016). Trench-parallel seismic anisotropy of the fast Swave was observed in many fore-arc areas and sub-slabs in subduction zones (Ando et al, 1983;Fouch and Fischer, 1996;Margheriti et al, 1996;Smith et al, 2001;Nakajima and Hasegawa, 2004;Long and van der Hilst, 2005;Abt et al, 2010;Long and Becker, 2010;Di Leo et al, 2012;Long and Wirth, 2013;Wagner Figure 9 (after Jung et al, 2010). The east-west direction corresponds to the lineation (L), and the north-south corresponds to the foliation normal.…”
Section: Geophysical Implicationsmentioning
confidence: 98%
“…It is interesting to see the changes in seismic anisotropy patterns; from trench-parallel S-wave anisotropy in the fore-arc area to the trench-normal S-wave anisotropy in the back-arc area (Smith et al, 2001;Nakajima and Hasegawa, 2004;Long and van der Hilst, 2006;Long and Wirth, 2013). This pattern of seismic anisotropy may be explained by the change in olivine CPO from Type-B in the fore-arc to Type-A, -C (or -E) in the back-arc (Kneller et al, 2005;Katayama and Karato, 2006;Kneller et al, 2007;Karato et al, 2008;Jung, 2012).…”
Section: Geophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation